PERAN AUDIT INTERNAL, PENGENDALIAN INTERNAL, DAN KOMITMEN ORGANISASI DALAM PENCEGAHAN KECURANGAN - Arief, Rachmat (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Internal audits help find deficiencies, internal controls set procedures to reduce risk, and organizational commitments to prevent fraud. Effective collaboration between the three allows the organization to protect its assets and reputation from fraud. The research aims to study the functions of internal auditors, internal controls, and organizational commitment in preventing and detecting fraud in property companies. This study adopts a quantitative approach with SmartPLS as a data analysis tool. This study uses a quantitative approach with the sample used are all internal auditors who work in private companies, namely commercial property or commonly called Malls in Depok City and processed using SmartPLS software. The findings of this study are that internal auditors and internal controls are affected by fraud prevention, and organizational commitment is not significantly affected by fraud prevention.